Economic evaluation of low-dose computed tomography for lung cancer screening among high-risk individuals – evidence from Hungary based on the HUNCHEST-II study - Péter Rózsa; Anna Kerpel-Fronius; Mátyás Péter Murányi; Ágnes Rumszauer; Gabriella Merth; Zsolt Markóczy; Péter Csányi; Krisztina Bogos (BMC Health Services Research)
Abstract Background Lung cancer (LC) is the leading cause of cancer-related death in Hungary. Early diagnosis of LC contributes to delivering survival benefits to patients. Low-dose computer tomography (LDCT) is an imaging technology that can be used to identify smaller nodules. The aim of this study was to investigate the cost-effectiveness of introducing organised LDCT screening in Hungary among individuals aged 50 to 74 years with high-risk for developing LC using clinical effectiveness and resource utilisation inputs based on the recent HUNCHEST-II clinical trial. Methods We estimated costs and outcomes in a cost-utility analysis framework over the time horizon of 30 years to compare annual and biennial screening for LC with LDCT against standard screening. The economic evaluation simulated a cohort of current and former smokers aged 50 to 74 years with a smoking exposure of at least 25 pack-years, using data from HUNCHEST-II, a multicentre study to evaluate the impact of LDCT screening on early detection of LC. Complementary data were retrieved from published studies and interviews with local experts. Results The results of the analysis are favourable from an economic perspective: the introduction of biennial screening for LC with LDCT yielded an incremental effectiveness of 0.031 QALYs as well as an increase in costs of 306 764 HUFs over the 30-year -time horizon when compared to standard screening. The value of the base case ICER (9 908 100 HUF/QALY) of biennial screening for LC with LDCT over standard screening was below the relevant cost-effectiveness threshold. Applying an annual screening strategy using LDCT yielded even more favourable cost-effectiveness results (ICER = 7 927 455 HUF/QALY) compared to biennial screening. Notably, the cost-effectiveness of biennial screening was extendedly dominated by annual screening. Conclusions Along with the mature data on its effectiveness, our analysis confirms that using LDCT for LC screening among high-risk individuals is a cost-effective alternative of standard screening in Hungary. Funding a nationwide lung screening program that uses LDCT is a justified decision in economic terms; annual screening would be the optimal strategy to maximize health benefits; however in case of limited financial resources, biennial LDCT screening could offer a cost saving alternative for marginally less health gains than annual screening.